Efektifitas Konstitusional Kebijakan Publik di Indonesia: Tinjauan Normatif atas Legal Gap dan Akuntabilitas Negara - Mutia Nur Fadhilah Ruslan (Indo Publishing, 2026)
This study aims to analyze the constitutional effectiveness of public policy in Indonesia through a normative examination of the phenomena of legal gaps and accountability gaps, while proposing a model for strengthening state accountability to ensure the realization of constitutional objectives. The research employs a normative legal method using statutory, conceptual, case, and limited comparative approaches. The legal materials consist of the 1945 Constitution of the Republic of Indonesia, relevant legislation, decisions of the Constitutional Court and the Supreme Court, as well as scholarly literature and official reports from state institutions. Data were analyzed using a normative-qualitative approach supported by gap analysis to identify discrepancies between legal norms (das sollen) and policy implementation (das sein). The findings indicate that the effectiveness of public policy cannot be assessed solely based on formal legality but must also consider functionality, accountability, and public participation as key indicators of constitutional effectiveness. The study reveals that legal gaps arise from regulatory disharmony, weak bureaucratic capacity, and institutional fragmentation, while accountability gaps result from fragmented oversight mechanisms that remain predominantly focused on administrative compliance. As its conceptual contribution, this research introduces the paradigm of constitutional effectiveness as a comprehensive framework for evaluating public policy, develops a typology of legal gaps and accountability gaps as analytical instruments, and proposes the concept of constitutional policy review as a post-implementation evaluation mechanism that complements judicial review. This model is expected to strengthen state accountability, enhance the quality of public governance, and ensure that public policies effectively realize constitutional values and the objectives of the state as mandated by the 1945 Constitution.